2019
DOI: 10.1111/jdi.12981
|View full text |Cite
|
Sign up to set email alerts
|

Association of renal arteriosclerosis and hypertension with renal and cardiovascular outcomes in Japanese type 2 diabetes patients with diabetic nephropathy

Abstract: Aims/Introduction The present retrospective study investigated the impact of renal arteriosclerosis ( AS ) and hypertension ( HT ) on long‐term renal and cardiovascular outcomes in Japanese type 2 diabetes patients with biopsy‐proven diabetic nephropathy. Materials and Methods A total of 185 patients were enrolled. Patients were divided into four groups stratified by renal AS status and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Although the exact reason for these ndings is not clear, we postulated one scenario. Atherosclerosis of the intrarenal and extrarenal arteries and microangiopathy of the glomerular capillaries, afferent arterioles, and efferent arterioles are considered to contribute to the progression of glomerular lesions in DN [37,38]. Previous studies have demonstrated that glucose uctuation is more signi cantly associated with atheroscleroticrelated diseases than the degree of hyperglycemic exposure as indicated by HbA1c levels in patients with type 2 diabetes [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact reason for these ndings is not clear, we postulated one scenario. Atherosclerosis of the intrarenal and extrarenal arteries and microangiopathy of the glomerular capillaries, afferent arterioles, and efferent arterioles are considered to contribute to the progression of glomerular lesions in DN [37,38]. Previous studies have demonstrated that glucose uctuation is more signi cantly associated with atheroscleroticrelated diseases than the degree of hyperglycemic exposure as indicated by HbA1c levels in patients with type 2 diabetes [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…For light microscopic examinations, renal biopsy specimens were stained with periodic acid Schiff, periodic acid silver methenamine, hematoxylin–eosin, and Mallory–Azan. The severity of IFTA was evaluated semi-quantitatively according to the pathological classification by the Renal Pathology Society as follows: score 0, no IFTA; score 1, < 25 %; score 2, 25–50 %, and score 3, > 50 % [ 6 12 , 17 , 18 ]. The severity of diffuse lesion was graded from 0 to 4 by the method of Gellman et al [ 7 , 17 – 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The severity of IFTA was evaluated semi-quantitatively according to the pathological classification by the Renal Pathology Society as follows: score 0, no IFTA; score 1, < 25 %; score 2, 25–50 %, and score 3, > 50 % [ 6 12 , 17 , 18 ]. The severity of diffuse lesion was graded from 0 to 4 by the method of Gellman et al [ 7 , 17 – 19 ]. Nodular lesion, exudative lesion, and mesangiolysis were scored as absent or present [ 7 , 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations